2022
DOI: 10.1007/s12665-022-10202-5
|View full text |Cite
|
Sign up to set email alerts
|

Crustal-scale thermal models: revisiting the influence of deep boundary conditions

Abstract: The societal importance of geothermal energy is significantly increasing because of its low carbon-dioxide footprint. However, geothermal exploration is also subject to high risks. For a better assessment of these risks, extensive parameter studies are required that improve the understanding of the subsurface. This yields computationally demanding analyses. Often, this is compensated by constructing models with a small vertical extent. This paper demonstrates that this leads to entirely boundary-dominated and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…A previously performed Sobol sensitivity analysis with the Saltelli sampler and 300,000 forward solves showed that the model is insensitive to eight of the 14 parameters (Fig. S1) 34 . We thus reduce the parameter dimension from 14 parameters to six.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…A previously performed Sobol sensitivity analysis with the Saltelli sampler and 300,000 forward solves showed that the model is insensitive to eight of the 14 parameters (Fig. S1) 34 . We thus reduce the parameter dimension from 14 parameters to six.…”
Section: Resultsmentioning
confidence: 94%
“…The highest uncertainties are between 30 and 35 km depth, where no interactions of the boundary conditions are observable. For a detailed investigation of the influence of boundary conditions on a geothermal conduction model, we refer to Degen et al 34 .…”
Section: Uncertainty Quantification Mapsmentioning
confidence: 99%
“…Options to address the parametrisation challenge also include surrogate models, parameter reduction, and model learning (e.g. Lu and Lermusiaux, 2021;Sun et al, 2021b;Albert et al, 2022;Degen et al, 2022;Liu et al, 2022). Surrogate models are learnt to replace a complicated model with an inexpensive and fast approximation.…”
Section: Quantifying Uncertainty Using Geohazard Modelsmentioning
confidence: 99%
“…Options to address the parametrisation challenge also include surrogate models, parameters reduction, and model learning (e.g., Lu and Lermusiaux, 2021;Sun et al, 2021b;Albert, Callies, and von Toussaint, 2022;Degen et al 2022;Liu et al, 2022). Surrogate models are learnt in order to replace a complicated model with an inexpensive and fast approximation.…”
mentioning
confidence: 99%
“…Surrogate models are learnt in order to replace a complicated model with an inexpensive and fast approximation. Parameters reduction is achieved based on either principal component analysis or global sensitivity analysis to determine which parameters significantly impact model outputs and are essential to the 160 analysis (Degen et al, 2022;Wagener, Reinecke, and Pianosi, 2022). Remarkably, versions of the model learning option do not need any prior information about model equations Eɱ but require local verification of conservation laws in the data ɗ (Lu and Lermusiaux, 2021).…”
mentioning
confidence: 99%